Gene expression correlates of facultative predation in the blow fly Chrysomya rufifacies (Diptera: Calliphoridae). Issue 15 (15th July 2019) - Pimsler, Meaghan L.; Sze, Sing‐Hoi; Saenz, Sunday; Fu, Shuhua; Tomberlin, Jeffery K.; Tarone, Aaron M.
Abstract: Effects of intraguild predation (IGP) on omnivores and detritivores are relatively understudied when compared to work on predator guilds. Functional genetic work in IGP is even more limited, but its application can help answer a range of questions related to ultimate and proximate causes of this behavior. Here, we integrate behavioral assays and transcriptomic analysis of facultative predation in a blow fly (Diptera: Calliphoridae) to evaluate the prevalence, effect, and correlated gene expression of facultative predation by the invasive species Chrysomya rufifacies . Field work observing donated human cadavers indicated facultative predation by C. rufifacies on the native blow fly Cochliomyia macellaria was rare under undisturbed conditions, owing in part to spatial segregation between species. Laboratory assays under conditions of starvation showed predation had a direct fitness benefit (i.e., survival) to the predator. As a genome is not available for C. rufifacies, a de novo transcriptome was developed and annotated using sequence similarity to Drosophila melanogaster . Under a variety of assembly parameters, several genes were identified as being differentially expressed between predators and nonpredators of this species, including genes involved in cell‐to‐cell signaling, osmotic regulation, starvation responses, and dopamine regulation. Results of this work were integrated to develop a model of the processes and genetic regulation controlling facultative predation. Abstract : In this work, we integrated field work, behavioral assays, and transcriptomic analysis of facultative predation in a blow fly (Diptera: Calliphoridae) to evaluate the frequency, utility, and correlated gene expression of facultative predation by the invasive species Chrysomya rufifacies . Field work observing donated human cadavers suggested facultative predation was rare in the wild, though the behavior was common in laboratory assays and demonstrated a direct fitness benefit (i.e., survival) for the predator under conditions of starvation. Furthermore, several genes were differentially expressed between actively predating and non‐predating individuals, including genes involved in cell‐to‐cell signaling, osmotic regulation, starvation responses, and dopamine regulation.